Analisis Faktor Internal Yang Mempengaruhi Tax Avoidance Pada Era 4.0 Pada Perusahaan Sektor Digital Teknologi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Maya Mustika; Sulistyowati Sulistyowati; Ananda Fasya Indira; Lina Noersanti; Juniarti Juniarti (Lembaga Penelitian Universitas YARSI, 2024)
This study aims to analyze internal factors that influence tax avoidance in the annual financial reports of digital technology sector companies listed on the Indonesia Stock Exchange for the 2018-2022 research period in the economy 4.0 era. The independent variables in this study are profitability, fixed asset intensity, and leverage. The approach used in this study is a secondary data quantitative approach. The population of the study was 73 digital technology sector companies listed on the Indonesia Stock Exchange in the 2018-2022 research period, and the sample was taken using the purposive sampling method with a total of 25 companies so that the number of observations in the study was 125 observation data. The data analysis technique uses panel data regression analysis using statistical calculations. The results of the research analysis prove that profitability and leverage have a partial and positive and negative influence on tax avoidance. In contrast, fixed asset intensity does not have a partial and negative influence on tax avoidance. The managerial implications are that the implementation of digital technology can help create a more transparent and accountable system, and the use of data-based audit technology can detect anomalies and potential tax avoidance earlier.